Answer:
It would be A, C, and D.
Step-by-step explanation:
Answer:
I. m = 2401
II. ((n+1) ∆ y)/n = 1/n[(n – y + 2)(n – y) + 1]
Step-by-step explanation:
I. Determination of m
x ∆ y = x² − 2xy + y²
2 ∆ − 5 = √m
2² − 2(2 × –5) + (–5)² = √m
4 – 2(–10) + 25 = √m
4 + 20 + 25 = √m
49 = √m
Take the square of both side
49² = m
2401 = m
m = 2401
II. Simplify ((n+1) ∆ y)/n
We'll begin by obtaining (n+1) ∆ y. This can be obtained as follow:
x ∆ y = x² − 2xy + y²
(n+1) ∆ y = (n+1)² – 2(n+1)y + y²
(n+1) ∆ y = n² + 2n + 1 – 2ny – 2y + y²
(n+1) ∆ y = n² + 2n – 2ny – 2y + y² + 1
(n+1) ∆ y = n² – 2ny + y² + 2n – 2y + 1
(n+1) ∆ y = n² – ny – ny + y² + 2n – 2y + 1
(n+1) ∆ y = n(n – y) – y(n – y) + 2(n – y) + 1
(n+1) ∆ y = (n – y + 2)(n – y) + 1
((n+1) ∆ y)/n = [(n – y + 2)(n – y) + 1] / n
((n+1) ∆ y)/n = 1/n[(n – y + 2)(n – y) + 1]
I believe the answer is 7 but I’m 99% sure ,
Sorry if it’s incorrect
Answer:
Step-by-step explanation:
Isn’t this mathematics not science
ANSWER:
A ) It also increases.
EXPLANATION:
When the measure of angle A increases im the trianes, the measure of angle A on line p also increases. This is angle A in the triangle and angle A on line p are equivalent to each other. Hence, if there is an increase to one of the angle As then there is also an increase to the other.
Therefore, the answer must be:
A ) It also increases.